Evaluation of the Clinical Efficacy of Multiple Lower Extremity Nerve Decompression in Diabetic Peripheral Neuropathy - Zhang, Wenchuan; Li, Shiting; Zheng, Xuesheng (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Background In 1992, Dellon reported the first use of peripheral nerve decompression surgery in the treatment of limb diabetic peripheral neuropathy (DPN). However, the efficacy of this procedure is still under debate. In this clinic study, we analyzed the therapeutic effect of microsurgical peripheral nerve decompression for DPN patients, using both clinical evaluation and electrophysiological testing.Patients and Methods In 560 patients with DPN , the surgical nerve decompression as described by Dellon was performed. Before and 18 months after surgery, Toronto Clinical Scoring System, quantitative sensory testing, and nerve conduction velocity tests were evaluated in all cases. The control group included 40 diabetic patients in the same age range but without DPN.Results The scores of nerve conduction velocity, quantitative sensory testing, and Toronto Clinical Scoring System improved significantly after microsurgical decompression of the entrapped nerves, although they were still worse than in the control group. According to the Wagner classification, 208 cases (37.1%) were rated as 1 (surface ulcer, no clinical infection) before surgery, but all were rated as 0 (no surface ulcer) 18 months after surgery.Conclusion Microsurgical decompression of entrapped peripheral nerves for DPN helped improve nerve conduction, restore lower limb feeling and motor function, and cure ulcers.
Keywords: diabetic peripheral neuropathy; nerve decompression; Toronto Clinical Scoring System; quantitative sensory testing; nerve conduction velocity